Dualism and cross-country growth regressions - Jonathan Temple; Ludger Wößmann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2006)
This paper develops empirical growth models suitable for dual economies, and studiesthe relationship between structural change and economic growth. Changes in the structureof employment will raise aggregate productivity when the marginal product of labourvaries across sectors. The models in the paper incorporate this effect in a moreflexible way than previous work. Estimates of the models imply sizeable marginalproduct differentials, and indicate that the reallocation of labour makes a significantcontribution to the international variation in productivity growth.
Keywords: O11; O40; 330; Structural change; dualism; wage differentials; TFP growth